2020
DOI: 10.1021/acs.jchemed.9b00643
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Solar Vapor Generation: Introducing Students to Experimental Procedures and Analysis for Efficiently Harvesting Energy and Generating Vapor at the Air–Water Interface

Abstract: Interfacial solar vapor generation has recently drawn much attention because of its high solar-to-vapor generation efficiency. Here we introduce the basic experimental procedures and analysis for undergraduates to perform such an experiment to catch up with the cutting-edge research wave. Interfacial solar vapor generation employs an interfacial solar vapor generator to localize the solar harvest and the vapor generation process at the air–water interface. In the experiment, three commonly seen black materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Tao et al 46,47 Considering that typical dimensions for laboratory scale (usually 1-4 cm of absorber diameter) of SWE systems were used in this study, and that the observed water F I G U R E 1 1 A, Average loss of mass, evaporation rate, and efficiency (inset) of pure water and simulated seawater (3.5% NaCl); eight evaporation cycles using pure water (B) and 4 evaporation cycles using seawater (C) for the SWE having 6.1 cm in diameter with 1 mm of thickness of the CF/PSty/Graphite 6 seconds sample [Colour figure can be viewed at wileyonlinelibrary.com] evaporation rate and efficiency could change in the scaling-up of the process, a SWE system of larger diameter using the CF/PSty/Graphite 6 seconds sample was prepared and tested for pure water and simulated seawater (3.5% NaCl) evaporation. The SWE system was placed on water in a 250 mL insulated beaker and exposed to the same light source.…”
Section: Reference Swe System Efficiency Observationsmentioning
confidence: 99%
“…Tao et al 46,47 Considering that typical dimensions for laboratory scale (usually 1-4 cm of absorber diameter) of SWE systems were used in this study, and that the observed water F I G U R E 1 1 A, Average loss of mass, evaporation rate, and efficiency (inset) of pure water and simulated seawater (3.5% NaCl); eight evaporation cycles using pure water (B) and 4 evaporation cycles using seawater (C) for the SWE having 6.1 cm in diameter with 1 mm of thickness of the CF/PSty/Graphite 6 seconds sample [Colour figure can be viewed at wileyonlinelibrary.com] evaporation rate and efficiency could change in the scaling-up of the process, a SWE system of larger diameter using the CF/PSty/Graphite 6 seconds sample was prepared and tested for pure water and simulated seawater (3.5% NaCl) evaporation. The SWE system was placed on water in a 250 mL insulated beaker and exposed to the same light source.…”
Section: Reference Swe System Efficiency Observationsmentioning
confidence: 99%
“…Membrane separation science is a field that focuses on the selective passage of chemical entities through specifically designed barriers, which are essentially two-dimensional in nature. This technology has played a pivotal role in addressing critical societal challenges, including clean water and air, public health, climate change, waste reduction, and energy generation. At the heart of this technology lies the membrane material itself. Covalent organic frameworks (COFs) are a distinct class of crystalline porous polymers constructed via a bottom-up method, utilizing molecular units with pre-established geometries that are interlinked through covalent bonds. The hallmark of COFs is their inherent ability to maintain precise positioning of their constituent building blocks in both two and three dimensions, allowing them to synthesize stable porous structures characterized by regularity. This property enables meticulous modulation of both the chemical and the physical attributes of the constructed network. Since the very first publication by Omar M. Yaghi in 2005, research on COFs has advanced beyond the synthesis and characterization of diverse structures and has extended into the realm of applied science. Because of their unique attributes, COFs have emerged as promising candidates for membrane construction, and membranes made from COFs have showcased groundbreaking results in fields such as desalination, resource element extraction, and energy conversion. …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, solar-driven interfacial evaporation technology has aroused much attention due to its advantages of eco-friendly features and low level of infrastructure. [8][9][10][11] The principle of solardriven interfacial evaporation technology is to convert solar energy into heat and localize the heat on the surface of interfacial materials to induce steam generation. Compared with the traditional solar-driven water treatment technology, the solardriven interfacial evaporation technology can significantly improve response time for steam generation and increase the solar-vapor conversion efficiency.…”
mentioning
confidence: 99%